Knowledge People with Type II Diabetes about the Importance of Herbs in Lowering Blood Sugar Levels - Rashid, Muna Salah (Journal for Research in Applied Sciences and Biotechnology, 2023)
At the moment diabetes has become an epidemic disease and according to recent statistics 400 million people have diabetes in the world and it is mainly associated with developing countries, Among the huge and heterogeneous numbers type 2 diabetes (T2DM) is the most prevalent, according to the Global Burden of Diseases study for the year (2016) it was found that T2DM and its complications were responsible for increasing the percentage of disability by 22% in the last ten years. This has greatly affected public health. For this reason, there was a need to make a questionnaire on the knowledge of people with type 2 diabetes (T2DM) of the importance of herbs in reducing blood sugar levels, and the research included 142 samples (individuals) who were asked questions in the form of an electronic questionnaire (google form) through social networking sites (Facebook, WhatsApp, Telegram, Messenger and others) and the questionnaire included questions about diet, symptoms and concomitant diseases in addition to whether the patient is taking drugs that lower the level of sugar in the blood as well as about the use of herbs by the patient and what they are These herbs and how much they amount per day, the average amount of herbs used by the patient was one cup, and the most important herbs used were turmeric and learners and led to a decrease in the level of sugar in the blood of the patient who used them. We conclude from this research that type II diabetes is most of its symptoms are frequent urination, thirst, slenderness, limb pain, in addition to limb neuropathy, while the diseases associated with this disease are high blood pressure, heart failure, kidney failure, visual impairment or blurred vision and other diseases.